Akulturasi Agama dan Budaya Lamaran Ngunggah- Ngungahi dalam Adat Kawin Colong di Banyuwangi - Qurrotul Ainiyah (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
Ngunggah-ngunggahi is a proposal tradition in the Osing Banyuwangi tribe called colong. The purpose of this study is to find out information about the thoughts of the Osing people about the relationship between religion and the culture of ngungggah-ngunggahi proposals. So that the customs carried out will be in line with Islamic teachings. With an ethnographic approach, this study produces; First, ngunggah-ngunggahi proposals are part of the colong marriage custom. This custom is carried out because the couple wants to get married, but does not get the blessing of the parents of the prospective bride. By carrying out the ngunggahi-ngunggahi custom, the Osing people have carried out a